2019
DOI: 10.1111/apt.15280
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effectiveness, safety and therapeutic drug monitoring of tioguanine in a cohort of 274 IBD patients intolerant for conventional therapies

Abstract: Summary Background Tioguanine (or thioguanine) is an alternative drug for IBD patients who fail prior conventional immunomodulating therapy. Aim To report effectiveness, safety and therapeutic drug monitoring in a cohort of patients with prolonged tioguanine maintenance therapy. Methods In this nationwide, multicentre study, medical records of tioguanine‐ using IBD patients were retrospectively reviewed. Response to therapy was defined as clinical effectiveness without (re)initiation of corticosteroids, concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
7
36
0
Order By: Relevance
“…The total rate of adverse events was relatively low for both tioguanine‐ (35 per 100 patient years) and LDTA‐ (37 per 100 patient years) treated patients. Simsek et al showed in a retrospective cohort of 274 tioguanine‐treated patient with 1567 patient‐years of follow‐up an adverse events rate of 12 per 100 patient years 19 . However, in this cohort, the median treatment duration was 51 months (IQR 36‐89).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The total rate of adverse events was relatively low for both tioguanine‐ (35 per 100 patient years) and LDTA‐ (37 per 100 patient years) treated patients. Simsek et al showed in a retrospective cohort of 274 tioguanine‐treated patient with 1567 patient‐years of follow‐up an adverse events rate of 12 per 100 patient years 19 . However, in this cohort, the median treatment duration was 51 months (IQR 36‐89).…”
Section: Discussionmentioning
confidence: 79%
“…For LDTA, a prospective (n = 74) and retrospective (n = 89) cohort of LDTA patients with prior failure to conventional thiopurines showed a discontinuation rate of 15% and 18% due to adverse events, respectively 17,18 . A retrospective cohort study of tioguanine‐patients conducted in the Netherlands showed a lower rate of adverse events requiring discontinuation (11%) 19 . However, in a systematic review of 353 tioguanine‐treated patients with median follow‐up between 3 and 22 months, approximately 20% discontinued treatment, mostly due to adverse events 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 50% of the azathioprine or mercaptopurine using patients discontinue treatment with these drugs, mainly due to adverse events [4]. Thioguanine (TG), an equally effective but better-tolerated thiopurine-derivative, has been proposed as an alternative treatment option for patients who failed previous traditional therapies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%